REAKSI PASAR MODAL INDONESIA TERHADAP PELUNCURAN RUDAL KOREA UTARA - Nicholas Arditya Dwianto; Ima Kristina Yulita (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2019)
This study aimed to examine the Indonesia capital market reaction to the NorthKorean missile launching. The type of this research is an event study by using themarket model estimation to estimate the expected return. This research used 100days as the estimated period and 9 days as the windows period. The sample of thisresearch consisted of 76 companies listed in the Index Kompas 100. The result shewthat the stock price did not react negatively toward North Korean missile launching.In this research, the emergence of disturbing events at t+3 and t+4 that North Koreasucceded in testing hydrogen bomb disturb the events observed by the author. At t+3 and t+4, the stock price react negatively and significantly. The result of thisresearch supported the Signaling theory that the information about a countrysparticular events such as information about North Koreas succes in testing ahydrogen bomb was interpreted as a negative signal (bad news)